Intermittent Theta-Burst Stimulation Over the Suprahyoid Muscles Motor Cortex Facilitates Increased Degree Centrality in Healthy Subjects - Zhang, Guoqin; Gao, Cuihua; Ruan, Xiuhang; Liu, Yanli; Li, Yuting; Li, E; Jiang, Lisheng; Liu, Lingling; Chen, Xin; Jiang, Xinqing; Xu, Guangqing; Lan, Yue; et al. (Frontiers in Human Neuroscience, 2020)
Theta-burst stimulation (TBS), a variant of repetitive transcranial magnetic stimulation (TMS), can potentially benefit the treatment of swallowing disorders. However, the after-effects of TBS on the swallowing motor cortex remain uncertain. The newly developed graph-based analysis of centrality approach has been increasingly used to explore brain networks. The purpose of this study was to identify degree centrality (DC) alterations in the brain network after different TBS protocols were performed over the suprahyoid muscles motor cortex in healthy subjects. A total of 40 right-handed healthy subjects (mean age: 23.73 ± 2.57 years, range: 21-30, 20 females) were included in this study and randomly assigned to two groups, including the continuous TBS (cTBS) group and the intermittent TBS (iTBS) group. All of the subjects underwent resting-state functional magnetic resonance imaging (rs-fMRI) scanning before and after TBS implementation. Compared to the baseline, cTBS resulted in increased DC values in the left inferior frontal gyrus (P < 0.01). In the iTBS group, decreased DC was observed in the left cerebellum and left medial frontal gyrus; However, increased DC was observed in a number of brain areas including the right superior temporal gyrus, right superior frontal gyrus, right postcentral gyri and left paracentral lobule (P < 0.01). These results indicated that cTBS mainly results in increasing DC in the ipsilateral. However, iTBS is capable of facilitating excitability of the swallowing motor cortex and increasing the connectivity of multiple brain regions, including the bilateral sensorimotor network, and might have therapeutic potential in the treatment of swallowing disorders.